Evaluation of the microbiological, nutritive and health properties of a millet-based fermented beverage - Mogashoa, Dipoelo (My University, 2024)
This study explored the potential of millet as a mainstream food source, emphasising its exceptional nutritional composition that promotes good health. The research focused on millet-based mageu, analysing two formulations: one with 90% millet flour and the other with 50%, over an 8-week storage period. The assessment included lactic acid bacteria (LAB), total aerobic bacteria, Escherichia coli, and moulds/yeasts. LAB were examined for probiotic traits like acid and bile tolerance, antibiotic susceptibility, and antioxidant activity. Chemical profile, nutritional, and sensory characteristics of mageu products were also evaluated. Viable LAB cells in both mageu formulations ranged from 193 × 104 to 24 × 106 CFU/mL, surpassing total aerobic bacteria (2.0 × 102 – 7 × 105 CFU/mL) and fungal counts (1.1 × 102 – 7.05 × 103 CFU/mL); E. coli was not detected. Identified as Pediococcus pentosaceus MD02 and Pediococcus acidilacti MD01, these LAB strains exhibited sensitivity at pH 1.5 for a short exposure time of 3 hours and tolerant to moderate acidity of pH 3 for a longer exposure time of 36 hours. The LAB strains further showed 40% – 90% survival rate in a low (0.3%) and high (0.9%) bile salt concentrations after exposure for short (24 hours) and longer (48 hours) periods. P. pentosaceus MD02 exhibited a higher antioxidant capacity of 38.85%. The strains showed resistance to streptomycin and penicillin. Mageu pH decreased from 4.2 to 3.2, and total titratable acidity increased from 0.16% to 0.27%. Antioxidant activity was lower than L-ascorbic acid. Proximate analysis revealed increased protein (42 – 58 μg/mL), crude fat (0.54 – 0.96 g/mL), moisture (85% – 99%), and ash (9.8% – 13%). Minerals (calcium, potassium, magnesium, sodium, phosphorus) ranged from 1.2 – 9.6 mg/mL, and sugars (glucose 2 – 47 mg/mL, sucrose 4 – 96 mg/mL) were detected. Sensory evaluation varied, with mageu 5:5 preferred. Millet-based mageu, fermented with LAB, demonstrated probiotic properties, nutritional value, and favourable sensory attributes and the natural bitter taste of millet was neutralised. Millet emerges as a highly nutritional alternative to staple cereals. This study highlights the potential of millet as a mainstream, health-promoting food source, addressing the demand for diverse and nutritious alternatives to traditional cereals like maize, sorghum, and wheat.
Thesis (M.Sc. (Microbiology)) -- University of Limpopo, 2024
Keywords: Escherichia coli; Good health; Antibiotic; Millet flour; Lactic acid bacteria; Food -- Microbiology; Fermented foods; Microbial sensitivity tests; Millets as feed; Lactic acid bacteria